If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -2)(x + -4) = 15 Reorder the terms: (-2 + x)(x + -4) = 15 Reorder the terms: (-2 + x)(-4 + x) = 15 Multiply (-2 + x) * (-4 + x) (-2(-4 + x) + x(-4 + x)) = 15 ((-4 * -2 + x * -2) + x(-4 + x)) = 15 ((8 + -2x) + x(-4 + x)) = 15 (8 + -2x + (-4 * x + x * x)) = 15 (8 + -2x + (-4x + x2)) = 15 Combine like terms: -2x + -4x = -6x (8 + -6x + x2) = 15 Solving 8 + -6x + x2 = 15 Solving for variable 'x'. Reorder the terms: 8 + -15 + -6x + x2 = 15 + -15 Combine like terms: 8 + -15 = -7 -7 + -6x + x2 = 15 + -15 Combine like terms: 15 + -15 = 0 -7 + -6x + x2 = 0 Factor a trinomial. (-1 + -1x)(7 + -1x) = 0Subproblem 1
Set the factor '(-1 + -1x)' equal to zero and attempt to solve: Simplifying -1 + -1x = 0 Solving -1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -1x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -1x = 0 + 1 -1x = 0 + 1 Combine like terms: 0 + 1 = 1 -1x = 1 Divide each side by '-1'. x = -1 Simplifying x = -1Subproblem 2
Set the factor '(7 + -1x)' equal to zero and attempt to solve: Simplifying 7 + -1x = 0 Solving 7 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -1x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -1x = 0 + -7 -1x = 0 + -7 Combine like terms: 0 + -7 = -7 -1x = -7 Divide each side by '-1'. x = 7 Simplifying x = 7Solution
x = {-1, 7}
| -42m-13=83 | | -192=-6(6x-4) | | 18x^2-12x^3+18=0 | | 633=9x+318 | | 18=w | | 18x^2-12x^3+3=0 | | G(-3)=3-27-3 | | 8^1/4-5^2/3 | | 84=4(1-4g) | | (b^4)^1/9=dsqrt(b^4) | | 2x+1.4=5.6 | | -1.2=1.8-3y | | 18=w/0.2 | | -9m-9=102 | | 587=8x+387 | | -2.8=5.2-2y | | -(-8x+4)+9x= | | -25=5(y-4) | | 4h-6=10n | | -12m-8=70 | | 0.16666666666(12-6x)=5(x+4) | | 0.33333333333(6y-9)=-2y+13 | | 80=2(n+6) | | -3.3=4.7-4y | | 6/(2a) | | .30=x(.14)+(1-x)(.05) | | 4x-11=15-9x | | -10500x^3+5000=0 | | 6+5z=8+5z | | 102x^2+6y^2+89y-322=0 | | 55x-39x+12=-64 | | -4=-2(5n-2)-8(-7n+1) |